Acute myocardial infarction in an 18 year old South Indian girl with familial hypercholesterolemia: a case report - Kumar, Anita A (BioMed Central, 2008)
Familial hypercholesterolemia is a single gene disorder with an autosomal dominant pattern of inheritance. Here we report an 18 year old South Indian girl who presented with myocardial infarction. She had xanthomas and an elevated serum low density lipoprotein cholesterol (LDL-C). Her mother and maternal uncle had died at a young age due to myocardial infarction. Her only sibling, 15 year old younger sister also had xanthomas and an elevated LDL-C. This report is to emphasise the need to clinically recognize xanthomas and its association with elevated LDL-C, premature atherosclerosis and familial inheritance. Early diagnosis and early initiation of treatment will save the affected individual and the other family members.